Implementing Writing Skills through The Genre Approach - Hidayad, Ferri; Agustin, Ariya; Despita, Despita; Purwanto, Muhammad Bambang (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Despite being largely regarded as a foreign language; English plays an undeniably significant part in Palembang's economy and educational system. Contrarily, research reveals that English proficiency among Palembang pupils’ declines. This article details a study that looked at how much EFL English majors at PGRI Palembang University improved their ability to write argumentative essays after being subjected to genre-based writing exercises with their writing instructors. The findings showed that students consistently struggled to criticize or refute opposing viewpoints and come up with more powerful rebuttals, even after being exposed to the preparation of genre-based argumentative essays. However, they were able to demonstrate development in their ability to recognize the rhetorical structures (genres) and lexicon-grammatical characteristics of the full argumentative essay. The strategy received favourable feedback from the participants. The paired sample t-test also revealed that students' post-intervention argumentative texts significantly outperformed their pre-intervention drafts. It is commonly accepted that students may regulate the linguistic aspects of the type of text with a specific communicative aim and comfortably enhance their writing skills by studying through a genre-based approach to writing. The consequences for teaching writing in an EFL setting are demonstrated in this essay. Additionally, it urges the adoption of a genre approach in EFL writing classes.